Modification of chlorine dioxide bleaching of Gmelina arborea (gamar) pulp (Bangladesh Journal of Scientific and Industrial Research, 2017)
Elemental Chlorine Free (ECF) pulp bleaching is now the dominant pulp bleaching process in globally. In most bleachery, chlorine dioxide is over-consumed. About two thirds of the chlorine dioxide is wasted in useless side reactions. In the study, kraft pulp from Gmelina arborea (gamar wood) was bleached by ECF bleaching in modified sequences. Oxygen prebleaching was carried out to decrease ClO2 requirement, which reduced kappa number of kraft pulp by 47.6% and increased pulp brightness by 21.7 percent points. Several sequences were tested based on the application of limited charges of ClO2 during successive ClO2and extraction stage. Application of this concept allowed a 33% reduction of ClO2 to reach target brightness. The kraft pulp could not reach target brightness of 80% in DED sequences using even 30 kg ClO2/ton of pulp, while splitting of same amount of ClO2 charge into DEDED sequences reached the pulp brightness to 81.1%. But oxygen delignified kaft pulp reached 79.6% brightness using 25 kg ClO2/ton of pulp in DED sequences. In the splitting of ClO2 charge into DEDED sequences, Oxygen pulp reached to 85% brightness by using only 20 kg ClO2/ton pulp.Bangladesh J. Sci. Ind. Res. 52(4), 247-252, 2017